EXPLORING THE RELATIONSHIP BETWEEN NUTRITION, LIFESTYLE, AND NON-COMMUNICABLE DISEASES - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Lifestyle factors such as diet and physical activity are important determinants of global morbidity from non-communicable diseases (NCDs). In this cross-sectional study, examines the association between nutritional intake, physical activity levels and NCD biomarkers (BMI, blood pressure, and fasting glucose) in a sample of 500 adults aged 20–60 years. Stratified random sampling was used to recruit participants, and dietary and physical activity intake data and health metrics were collected using standardized assessments and clinical measurements. Both insufficient nutrition and low physical activity independently predicted higher BMI, blood pressure and fasting glucose levels. In addition, participants with poor nutrition and low physical activity levels had the highest odds ratios for elevated BMI (OR = 2.7), hypertension (OR = 3.4) and elevated glucose (OR = 3.1), indicating a synergistic effect that increases NCD risk. These findings thus call for simultaneous targeting of both dietary quality and physical activity for NCD prevention through dual targeted public health strategies. Integration of these lifestyle factors into integrative interventions may be critical to a reduction in NCDs prevalence and overall population health.